Leadership and commitment on Portuguese rugby national team - Carvalho, M.; Martins, L.; Portela, S. (International Journal of Academic Research, 2013)
This research aims to get empirical relationships between the influence of leadership attributes of the Portuguese Rugby Head Coach on commitment of the National team players concerning the Team performance and consequently the degree of commitment of the National Team players. The Team targets are considered to be short and medium-term delineated. Therefore, this paper attempts to answer three questions: a) the dimensions of commitment most valued by players in the National Rugby Team; b) the identification of the existence of a charismatic leadership in the National Rugby Team, having in mind the attributes that can define it; c) the identification of the existence of "social exchange", recognized by players and the Head Coach and its influence on the dimensions of commitment in the Team. Data were collected by using four questionnaires enquired to each player referring to the theoretical models characterized in the literature review. Twenty-four players answered to the questionnaire. It was found that the normative commitment of the Team is slightly more valued by the players than the affective component, and their leader`s performance profile is considered charismatic. The empirical evidence suggests that the relationship between the leader and players is guided by social changes, which may contribute to the sporting success of the National team in short and medium-terms.